Project-Based Learning Electronic Thematic Student Worksheets (E-Book PJBL) Improving Critical Thinking Skills - Siki.A. Novinda Putri; Putu Nanci Riastini; Made Vina Arie Paramita (International Journal of Elementary Education, 2022)
The low critical thinking skills are caused because students being less interested in learning. A lack of learning resources causes students' lack of interest in learning. This research aims to develop E-LKPD based on Project Based Learning. This type of research is developed using the ADDIE model. The trial was conducted using a pre-experimental design, one shoot case study2 validators, and 2 practitioners who carried out the content validity test of the PjBL E-package products. The subject of the product trial was fourth-grade elementary school students. The data collection method in this research uses critical thinking tests, qualitative observations, quantitative observations, interviews, questionnaires/questionnaires, and document studies. The instruments used in collecting data are rating scales, interview guidelines, questionnaires, test question sheets, and document study sheets. The techniques used to analyze the data are data analysis of the validity and reliability of the instrument, qualitative descriptive analysis, quantitative descriptive analysis, and t-test. The results of data analysis are the results of product content validity analysis, namely 1.00 (very high). The result of the teacher's response is 3.85 (very good), and the student's response is 3.56 (very good), so it is feasible to use. The result of the effectiveness test is the probability value or Sig. (2-tailed) of 0.000, this probability value is smaller than the 0.05 significance level. It means there are differences in the critical thinking skills of fourth-grade students after learning to use the PjBL E-Package. In other words, the PjBL E-Packet can improve students' critical thinking skills.